Effectiveness of Riboflavin and Rose Bengal Photosensitizer Modified Adhesive Resin for Orthodontic Bonding - Ali Alqerban (MDPI AG, 2021)
This study aimed to evaluate the effect of riboflavin (RF) and Rose Bengal (RB) photosensitizer modified adhesive resin on the degree of conversion (DC), and antimicrobial capacity after bonded to tooth surface. Different concentrations of RB and RF were prepared by homogenization method. An ultraviolet light source A (UVA) (375 nm wavelength, 3 mW/cm2 power) was used for 30 min irradiation. FTIR was performed for control and test adhesives to analyze the DC. Antibacterial testing was performed using the MTT assay. Metal brackets were bonded using the modified adhesives and subjected for SEM examination. The surfaces of teeth and metal brackets were examined at ×10 magnification for assessing adhesive remnant index (ARI) after PDT, 24 h and thermocycling. For DC, control group, 0.1% RB and RF after PDT showed the highest value. SEM imaging indicated lowest growth of Streptococcus mutans over 0.5% of RB-PDT and RF-PDT as compared to the control group. The MTT assay outcomes reported that the activity of S. mutans substantially decreased with the addition of a high amount of either RB or RF (p < 0.01). Mean ARI scores showed a significant difference between all groups. This study concluded that 0.1% of either RB or RF after PDT can be used for bonding orthodontic brackets to the tooth surface with substantial antibacterial properties.